Weathering the Storm Together: How Emergency Nursing is an Interpretive Practice - Lisa Alphonsus (University of Calgary, 2021)
This paper was written for a hermeneutic research course in response to the statement: Emergency nursing is an interpretive practice. In it, I share from my own experience as an emergency department nurse, sharing deeply reflective and profound examples illustrating how I have come to understand the practice of interpretation. Drawing on other works within philosophical hermeneutics, I explore how emergency nurses bring our backgrounds and prejudices to work, and how we create meaning together with our patients. Gadamer’s description of the hermeneutic circle is used to explore how nurses move back and forth between the part and the whole, both as ourselves as nurses and how we care for our patients. The importance of emergency nurses remaining vulnerable, despite the acuity and chaos in which we are often surrounded, is emphasized, as well as supporting emergency nurses in our work, in our care for our fellow humans.